Choriocarcinoma metastatic lung, kidney, and small intestine (jejunum) - Molina, Nancy (2015)
We present the case of a 39 years-old patient who had had molar pregnancy 7 years before and presented no with six-month genital blood loss, melena and severe anemia. Pathological examination revealed metastatic choriocarcinoma to lung, kidney and Jejunum.